Pengembangan Media Pembelajaran Flipbook Digital Pembuatan Chiffon Cake - Dinanti, Putri Zahra; Artanti, Guspri Devi; Febriana, Rina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to develop and test the feasibility of products in the form of digital flipbook learning media for making chiffon cake. This media was developed using the Research and Development (R&D) model with the ASSURE development method by Heinich Heinich, Molenda, Russell, and Smaldino. The stages of this research consist of Analyze learner characteristics, State objectives, Select, or modify design media, Utilize media, Requires learner response and Evaluate. The resulting media consists of 3 parts, namely the introduction, core and closing parts. The teaching media was validated by expert examiners with a score of 98% for material aspects, 95% for media aspects and 97% for language aspects. The results of the one to one test assessment response by learners were 92%, the small group test was 93% and the field testing test was 92%. Based on the test results, it can be concluded that the development of a digital flipbook for making chiffon cake is categorized as very feasible to use as media in the subject of Indonesian Cake and Cake Products at SMK Negeri 70 Jakarta.